Modelling and Simulation of Micro Gas Turbine Performance and Exhaust Gaseous - Kit L.W.; Mohamed H.; Luon N.Y.; Hasini H.; Chan L. (Semarak Ilmu Publishing, 2024)
Numerical simulation of cold flow and explosion in a Capstone C30 micro gas turbine is simulated using OpenFOAM. This study is aimed to investigate the combustion of non-premixed methane/air inside a micro gas turbine. The combustion characteristic inside a micro gas turbine with 100% methane is assumed for the fuel is studied with a three-dimensional model of micro gas turbine. The velocity of the flow increases significantly in the explosion simulation where the combustion of non-premixed methane/air mixture is initialised. The temperature in the micro gas turbine increased to 2400K at the downstream of inlets and reduces to 1500K at the combustion zone. High concentration of CO and CO2 is in the main reaction zone. The fraction of water vapours and hydroxyl on the other hand is lower compared to other species. 2023, Semarak Ilmu Publishing. All rights reserved.